INFORMASI POTENSI INDUSTRI KREATIF BERBASIS WEBLOG DI KABUPATEN BATANGHARI PROVINSI JAMBI - siti hamia ulfa; Ahyuni Ahyuni (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
The purpose of this study is to determine the potential of the creative industries in Batanghari Regency and the form inform of the creative industry weblog based in Batanghari Regency.. This type of research is a descriptive study with a mixed method. Data collection techniques are carried out with observation, in-depth interviews and documentation. Data analysis tools used in this study with scoring analysis and tipology analysis. Data analysis techniques to consist of The result showed that (1) Batanghari Regency has enormous potential in the creative industries. The creative industries owned by Batanghari Regency consist of culinary, handicraft, fine arts and photography subsectors. (2) Potential of the creative industry drawing in weblog was the created to provide information related to creative industry activities in Batanghari Regency.